2009
DOI: 10.2119/molmed.2009.00035
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory NK-Cell Functions in Inflammation and Autoimmunity

Abstract: Natural killer (NK) cells were viewed traditionally as cytotoxic effector cells whose rapid killing of infected and transformed cells without preactivation provides a first line of defense prior to the initiation of an adaptive immune response against infection and tumor development. However, it has become clear that NK cells interact with various components of the immune system, and therefore have the potential to function as regulatory cells. While NK cells can assist in dendritic cell (DC) maturation and T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 88 publications
0
70
0
1
Order By: Relevance
“…More recently though, the current work on NK cells points firmly towards a disproportional, maintained activating signaling in patients with different autoimmune diseases. Therefore, hyperactivated NK cells could directly cause tissue damage by uncontrolled cytotoxic response but also modulate the immune response [11], mostly after TLR stimulation [19] in the interaction with antigenpresenting cells and T cells, via direct cell-to-cell contact or via cytokine production. In line with this premise, we found an increased activation of CD56 + cells after TLR1/2 and to some extent after TLR7/8 stimulation that allow a clear differentiation and separation of definitive SSc from HC and PRP subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently though, the current work on NK cells points firmly towards a disproportional, maintained activating signaling in patients with different autoimmune diseases. Therefore, hyperactivated NK cells could directly cause tissue damage by uncontrolled cytotoxic response but also modulate the immune response [11], mostly after TLR stimulation [19] in the interaction with antigenpresenting cells and T cells, via direct cell-to-cell contact or via cytokine production. In line with this premise, we found an increased activation of CD56 + cells after TLR1/2 and to some extent after TLR7/8 stimulation that allow a clear differentiation and separation of definitive SSc from HC and PRP subjects.…”
Section: Discussionmentioning
confidence: 99%
“…NK are able to release a wide variety of cytokines upon different activating triggers and to tune the maturation of other cells of the immune system, such as DC and T cells, skewing them into a pro-inflammatory or tolerogenic status or into different Th patterns of activation [11]. NKT-like cells are a broad, diverse group of T cells co-expressing T cell receptor and NK receptors, which cluster very close to NK cells in terms of multiparameter surfacemolecule expression, but exhibit a relative transcriptional quiescence, requiring a more pro-inflammatory milieu to exert similar immunoregulatory properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…NK cells were first named for their ability to kill target cells without preactivation (Kiessling et al 1975a, b). Two main subsets have been described, CD56 bright and CD56 dim NK cells, which have distinct phenotypes and functions (reviewed by Lünemann et al 2009). Precursors of human NK cells develop in the bone marrow and then are thought to migrate to secondary lymphoid organs, e.g., tonsils, where they mature before egressing to the peripheral blood to patrol the body for intruding pathogens and emerging cancer cells (Carrega and Ferlazzo 2012;Freud et al 2014).…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…Since our results indicated that NK cells do not affect the host innate immune response to HMPV, we wondered whether NK cell depletion would alter the adaptive immune response. T CD8 cells are important for HMPV clearance during primary infection (40); furthermore, the absence of NK cells alters the number of T CD8 cells responding to other viruses (41)(42)(43)(44)(45)(46). To study the T CD8 cell response, we used an HLA B7.2 transgenic (B7tg) mouse model (47) in which the M 195-203 (M195) peptide is the immunodominant HMPV epitope (13).…”
Section: Nk Cells Do Not Modulate Lung Histopathologymentioning
confidence: 99%